Association Between Comorbidities and Outcome of COVID-19 Patients at dr. M. Djamil General Hospital Padang - Nova Indriyani; Yessy Susanty Sabri; Afriani Afriani (Respiratory Science, 2022)
Background: COVID-19 has spread rapidly throughout the world with high morbidity and mortality estimated up to 20%. This number will increase with the presence of comorbidities. Comorbidities were associated with complex clinical management and impacted on COVID-19 disease outcomes. This study aims to determine the association between comorbidities and the outcome of COVID-19 patients at Dr. M. Djamil Hospital. Method: We conducted an observational study with a retrospective cohort design on COVID-19 patients treated at Dr. M. Djamil Hospital. Data were taken from medical records from January to March 2021. Association between comorbidities and the outcome of COVID-19 patients was analyzed by Chi-Square or Fisher Exact Test. Results: The majority patientss were female (56.4%) and ages above 50 years old (64.3%) were the majority of patients. The most common was hypertension (36.56%). The longest length of stay of COVID-19 patients was more than 21 days (52.9%).  The outcomes of COVID-19 patients were recovered (59.5%), recovered with sequelae (5.7%), and died (34.8%). Diabetes mellitus affected the end of treatment outcome. There was no relationship of type of comorbidity with length of stay. The more co-morbidities a patient suffers, the condition when infected with COVID-19 will get worse. Conclusion: The number of comorbidities affects the outcome of COVID-19 patients. Diabetes mellitus is most common that affects the end of treatment outcome for COVID-19 patients at Dr. M. Djamil Hospital.